Maximizing Culinary Business Profit with the POM-QM Simplex Method - Fredy; Kevin; Limba Jaya, Sartito; Angie, Supenatus; Ramayani, Nadia; Effendy, Dudy (Journal Economic Business Innovation, 2024)
Optimizing profit in Micro, Small, and Medium Enterprises (MSMEs) poses a common challenge for owners, particularly in the culinary sector. This study explores the potential application of the simplex method to maximize profits in "Martabak Pak Amir," a Martabak business. Utilizing POM-QM software, the research identifies key variables influencing Martabak business profits, including production costs, selling prices, production time, and profits from three Martabak variants. The simplex method, a linear programming problem-solving approach, iteratively develops solutions to achieve optimal outcomes. Data collected from observations and interviews with Martabak Pak Amir over a two-week period are utilized. The enterprise offers three Martabak variants: chocolate, pandan, and cheese. Through linear programming and simplex method analysis, the optimal calculation reveals that producing the pandan variant three times yields a maximum profit of Rp 8,100,000 monthly, with total monthly sales of Rp 4,764,000 or 397 portions of pandan Martabak sold per month.